Pendidikan Spiritual Anak Usia Dini Dalam Perspektif Al-Qur’an - Halim, Junaiji Abd. (LP2M STAI Darul Kamal NW Kembang Kerang, 2023)
Early childhood spiritual education in the perspective of the Qur'an is an educational process that emphasizes cultivating the child's spiritual potential that he has brought from birth through inculcating religious spiritual values which include Aqidah, Faith, Islam and Ihsan which are applied directly to children. early childhood, as an effort to animate and develop the natural potential of children who are carried from birth. Spiritual education will not grow by itself without guidance from divine revelation. Spirituality that is taught without involving the guidance of divine revelation will be limited only to the view of logic. Then this spiritual will be dry and far from the guidance of the Creator. So spiritual education must be taught and developed through spiritual education that comes from religious teachings, because spirituality is closely related to divinity. To revive the spirituality of early childhood can only be done through inculcating religious spiritual values such as teaching faith, Islam and sincerity, because these three sources are known as religious foundations. Thus this research is different from the view which states that: to revive spirituality does not require the role of religion.